2009
DOI: 10.1242/jeb.022582
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of food provisioning of honeybee larvae by worker bees

Abstract: SUMMARYAlthough it has clearly been demonstrated in previous studies that honeybees inspect their worker brood in a non-random fashion, it is still unclear which signals and cues worker bees use to monitor the nutritional state of their brood. Here we show that worker bees can recognize and quantify the larval food present in a brood cell olfactorily and identify potential mechanical signals produced by the brood. There is no evidence for additional chemical hunger signals produced by the larvae. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…Removal of treated larvae by workers could occur because of a change in the characteristics of larvae that nurses would recognize (e.g. behavior [ 52 ] or chemical profiles [ 27 , 53 ]). Here, we observed that larval pyriproxyfen treatment induced a higher and dose-dependent rejection rate of reintroduced adults by nestmates.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of treated larvae by workers could occur because of a change in the characteristics of larvae that nurses would recognize (e.g. behavior [ 52 ] or chemical profiles [ 27 , 53 ]). Here, we observed that larval pyriproxyfen treatment induced a higher and dose-dependent rejection rate of reintroduced adults by nestmates.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential links between pesticides and bee declines, toxicology information on honey bee larvae is scarce and detoxification mechanisms in this development stage are virtually unknown. Due to the characteristic intensive brood care displayed by honey bees (Heimken et al, 2009), it is generally assumed that the larvae rely on adult bees to detoxify for them and that this development stage exhibits a diminished ability to detoxify dietary toxins. Most published work in this area tends to focus exclusively on adult bees and on the acute toxicity of dietary toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering investigations demonstrated that hornet larvae may communicate via substrate vibrations, by showing that Vespa orientalis larvae perceive vibrations and respond to them by emitting their own substrate-borne vibrations, which can be produced by body contractions and by scratching on the paper nest (Ishay and Ikan, 1968;Ishay and Landau, 1972;Ishay and Brown, 1975;. Subsequently, hunger signals of varying nature have also been demonstrated for ants (Cassill and Tschinkel, 1995;Kaptein et al, 2005), bumble bees (Pereboom et al, 2003) and honeybees (Huang and Otis, 1991;Heimken et al, 2009). The opposite situation, however, that adults produce signals to communicate with larvae, has been poorly investigated and our results open a new intriguing research avenue.…”
Section: Discussionmentioning
confidence: 99%